Viscous fragmentation and topology-induced residual gas trapping during gas–water displacement in fracture networks - Kangsheng Xue; Hai Pu; Yanlong Chen; Ming Li; Yu Wu; Lulu Liu; Qingyu Yi; Zheng Ma (Advances in Water Resources, 2026)

The Identification of Digramma interrupta (Diphyllobothriidae: Ligula) in a Captive Red-Crowned Crane and a Crucian Carp Reveals a New Case for Co-Occurrence - Maolin Lu; Yuling Yang; Mengchao Zhou; Yaxian Lu; Honyan Yu; Ruisi Zhang; Tianlu Liu; Mengru Zhao; Lei Han; Zhijun Hou (Acta Parasitologica, 2026)

The regulation of CgmiR-29 in glycogenolysis in the Pacific oyster under high-temperature stress - Hairu Xu; Lei Gao; Xingyi Feng; Jiayu Ye; Honglu Liu; Mingyan Bao; Lingling Wang; Linsheng Song (Aquaculture, 2026)

Simulated plant-derived exudate pulses promote maize phosphorus uptake by recruiting specific rhizosphere microbial communities and shaping root metabolites - Guiwei Wang; Yuechao Yang; Chenghao Liu; Zekun Wang; Lu Liu; Xiaoqi Wang; Yuanyuan Yao (Applied Soil Ecology, 2025)

Assessing Changes in China's Pond Water Quality From 1989 to 2020: Implications for Green Development in Aquaculture - Yuanshuai Duan; Lu Liu; Rong Tang; Shouqi Xie; Mingmei Yang; Zhimin Zhang; Dapeng Li (Reviews in Aquaculture, 2025)
Since 1989, China has become the world's largest aquaculture producer through pond culture, significantly contributing to global food security but potentially posing environmental threats. However, little is known about the changes in the pond water quality at broad spatial and temporal scales, thus creating challenges in the sustainability of pond aquaculture. Herein, we explore changes in water quality in China's aquaculture ponds from 1989 to 2020 and assess the waterbody's health status to optimize sustainable management strategies. This study highlights pond water quality changes closely associated with China's aquaculture practices, development, and related policies. Seasonal and regional farming variations significantly impact water quality, with peak aquaculture seasons and Central China and North China associated with the lowest water quality scores. Pond water quality initially declined with the rise of intensive aquaculture but improved after 2012 with the adoption of ecological engineering measures, eco‐farming practices, and policies supporting green development. Under a scenario combining these efforts, the water quality score in 2035 is projected to increase by 57% of the 2020 level. These findings reveal that national ecological initiatives and advancements in green aquaculture techniques and public policies can significantly enhance the water quality of China's aquaculture ponds, offering valuable insights into environmental governance in global agriculture.

Coupling a light use efficiency model with a machine learning-based water constraint for predicting grassland gross primary production - Ruiyang Yu; Yunjun Yao; Qingxin Tang; Changliang Shao; Joshua B. Fisher; Jiquan Chen; Kun Jia; Xiaotong Zhang; Yufu Li; Ke Shang; Junming Yang; Lu Liu; et al. (Agricultural and Forest Meteorology, 2023)